As voces da (des)cortesía en galego L2: aspectos sociodiscursivos - Castro Lorenzo, Laura (Madrygal. Revista de Estudios Gallegos, 2020)
In this article, we reflect on how a group of Galician L2 students, all of them coming from outside Galicia, understand, perform and build pragmatic politeness and impoliteness. In this regard, we examine a series of semi-directed interview samples, conducted with students of the Official Language School (Escola Oficial de Idiomas) in Santiago de Compostela. Some preliminary considerations, intended to introduce the reader to the empirical and epistemological context in which this work was developed, are exposed in the first two sections. Then, in the first information block (section 3), after reviewing some of the most important theoretical approaches to (im)politeness, we focus on some informants’ metapragmatic narratives, trying to address the normative aspects related to the (im)politeness phenomenon from a socio-discursive point of view (3.2, 3.3 e 3.4). In the second part of this article (section 4), we explore the theoretical relationship between the concepts of face and identity (4.1) and analyze excerpts from the corpus relying on these interpretative frameworks, in order to establish the impact of face vulnerability (4.2), linguistic and sociocultural variation and different kinds of identity discourses (4.3) on the negotiation of relational roles related to the pragmatic (im)politeness in intercultural contact situations.